Pengaruh Sales Growth dan Likuiditas terhadap Profitabilitas - Muhamad Sahrul Ramdani; Erry Suryana; Dicky Jhoansyah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
This study aims to determine the effect of Sales Growth (X1) and Liquidity (X2) on Profitability (Y) of PT Smartfren Telecom Tbk. The object of this study is PT Smartfren Telecom Tbk which is listed on the Indonesian Stock Exchange for the 2014-2021 period. The method used in this research is descriptive and associative with a quantitative approach. The sample used is PT Smartfren Telecom Tbk with a population of 32 using the natural setting technique with multiple linear regression data analysis techniques, multiple correlation coefficients, coefficient of determination and to test the research model using the F-Test and for testing the hypothesis using the T-Test using the application SPSS 21 software. The results of this study show that there is no significant effect on the Sales Growth and Liquidity variables on Purchase Decisions with the results Fcount 0.501 < Ftable 3.328 and the results of research on testing the T-Test Hypothesis on Sales Growth variables (X1) on Profitability Variables (Y) there is no significant effect, and on the variable Liquidity (X2) on Profitability (Y) there is no significant effect.